Nature and culture intertwined or redefined? On the challenges of cultural primatology and sociocultural anthropology - Gabriela Daly Bezerra de Melo (Revue de Primatologie)
The modern categorization also referred to as modern constitution has set Nature and Culture apart as two distinct ontological provinces, separating the pole of human beings and culture from the pole of non-humans and nature. Recent sociocultural anthropology and social studies of science have revisited the historical abyss between Nature and Culture and have shed light on the manifold conceptualizations of both terms across human cultures. For instance, non-Western indigenous relationships between humans and non-human animals have blurred the boundaries of continuity and discontinuity, supporting a hybridization of the modern Nature-Culture poles. Moreover, social studies of science have insisted that scientific practice is permeated by problems that are neither “natural” nor “social” because Nature and Culture become part of the inquiry, not the solution. If any interdisciplinary exchange is to be set in motion between cultural primatology and sociocultural anthropology a re-conceptualization of Nature and Culture should be called for. Whereas cultural primatology traditionally employs paradigms long abandoned by sociocultural anthropology, leading to a simplistic naturalization of culture in the eyes of anthropologists, it can be said that cultural anthropology remains reluctant to engage in dialogue with life sciences, alarmed it might be reduced to them. To this extent, primatological models of culture that emphasize social learning over methods of elimination appear to meet a demand.  Nature and Culture have become intertwined, but between an over naturalized culture of primatologists and a super socialized culture of anthropologists lays the challenge of redefining both Nature and Culture.